Site selection for the Small-Scale Aquaculture Farming Systems in the Western Cape : a GIS application - Steer, Lorn Adam (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2006.